UX-Tips: uma técnica de avaliação de user experience para aplicações de software - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
User Experience (UX) is one of the most important software quality attributes used when designing, describing, or improving how users feel when interacting with a system, focusing not only on tasks and their accomplishment, but also considering emotional aspects of the interaction. The evaluation of UX plays an essential role in the improvement and development of interactive applications. The UX evaluation aims to identify how users apply, perceive and learn such applications, allowing them to evolve and adapt to user expectations. However, most of the proposed techniques are intended to evaluate UX only considering the emotional aspects aroused in the user when interacting with an application. In this way, such techniques do not allow the identification of possible problems that users might have faced and generated a negative experience. Consequently, it is not possible to know which aspects need to be improved for the application to provide a positive user experience. With this motivation, this research presents the development of a technique to evaluate the UX of software applications called UX-Tips (User eXperience Technique for Interactive Products). The goal of this technique is not only to verify the emotional aspects, which indicate just if the experience was positive or negative, but to allow the identification of the problems that possibly generated a negative experience with the application, allowing it to be improved from the perspective of the user. We hope to contribute to the improvement of the software quality, in order to make it more pleasant for the user and allowing a more pleasurable experience when interacting with it. We carry out three empirical studies to evaluate the feasibility of the proposed technique, analyzing whether it enables an evaluation to be performed that identifies the problems that may have affected UX. The results obtained through these studies showed that UX-Tips supported evaluating the UX and allowed users to report problems that affected their experiences.
UX-Tips: a user experience evaluation technique for software applications
Keywords: Experiência do usuário; UX (User Experience); Qualidade de software; Fatores de UX; Técnica de avaliação de UX; User eXperience; Software quality; UX factors; UX evaluation technique; CIÊNCIAS EXATAS E DA TERRA: CIÊNCIA DA COMPUTAÇÃO